2012
DOI: 10.1007/s13139-012-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Criteria on 18F-FDG PET/CT for Differentiating Benign from Malignant Focal Hypermetabolic Lesions of Parotid Gland

Abstract: Uptake patterns and margins on CT are useful PET/CT diagnostic criteria for differentiating benign from malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Salivary gland tumors are rare, constituting about 3% of all head and neck carcinomas [1–3]. Most of these lesions originate from the parotid gland, with approximately 75% being benign [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Salivary gland tumors are rare, constituting about 3% of all head and neck carcinomas [1–3]. Most of these lesions originate from the parotid gland, with approximately 75% being benign [1].…”
mentioning
confidence: 99%
“…Although most parotid tumors are glandular in cause, squamous cell carcinoma represents most FDG-avid head and neck tumors overall [2]. The controversy surrounding the role of FDG PET/CT in the assessment of parotid tumors results from the fact that some malignant tumors present as non-FDG-avid lesions [2, 3, 7]. …”
mentioning
confidence: 99%
“…Imaging techniques established the site of origin of these tumors with 96% accuracy 14 . Prior to the CT era, very limited radiologic information could be gleaned from plain films and multidirectional tomograms 15 . The degree of lesion vascularity could be identified on a conventional angiogram; however, only a lesion such as a paraganglioma, with its characteristic hypervascular appearance, or an aneurysm could be confidently diagnosed 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in case of high-grade SGT, cervical LN staging needs more sensitive diagnostic modality, and FDG PET/CT may be helpful. It is difficult to distinguish between benign and malignant SGT on F-18 FDG PET/CT because benign tumors such as Warthin's tumor may also show high glucose metabolism [19][20][21]. However, recent studies have demonstrated that F-18 FDG PET/CT has a significant effect on the management of patients with malignant SGT in initial staging and followup compared with conventional imaging studies [6,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%